Media format matters: Users' perceptions of physical versus digital games. Issue 1 (27th December 2016) - Lee, Jin Ha; Holmes, Dylan; Lobe, Brooks
ABSTRACT: Despite the rapid shift in media distribution from physical to digital formats, few studies explore what this means to users with regards to perceived values, limitations, and experience with media. We investigate this problem, specifically within the context of video games, aiming to understand which formats game players prefer and for what reasons, and the implications for game content providers and digital libraries. The findings from a survey of 1, 257 game players showed that more respondents preferred digital formats over physical formats. Advocates of digital games typically valued accessibility and convenience, longevity of games free of physical damage, less need for storage, and reduced cost. Advocates of physical games generally valued the ability to easily retrieve, share, and resell games, ownership and longevity of access to games, the paraphernalia and collectibles that came with physical games, and the aesthetic and tangible qualities of the physical object. We discuss the implications of these findings for content providers and libraries, with an emphasis on game preservation efforts.